Gender-based role perceptions in financial management of Filipino households - Zipagan, Carla Janine T.; Dare, Evangeline M. (Quezon City College of Home Economics, University of the Philippines Diliman, 2016)
Household financial management has always been a significant aspect of family resource management. The knowledge of all members of the household regarding effective financial management is vital especially amidst the varying needs of the family. For an effective management of resources to take place, members of the households, regardless of the gender, must be aware of the practices that should be done. This will only be attainable if gender stereotypes within the home are eliminated. One hundred Grade 10 students comprised the population under study for this research. It has been found that mothers take the role of financial managers and primary decision-makers for the household. The decisions of both parents, however, are needed in tasks with higher financial risks. It is interesting to take note that there is an adequate statistical evidence to claim that there is a difference with the responses of male and female children as to how they perceived the tasks performed by mothers and fathers. Based on the test for independence (chi square), the male respondents viewed their fathers to be the primary decision-maker in financial-related matters. Conversely, the female respondents perceived their mothers as the one making financial decisions for the household. The results showed the respondents' tendencies to view financial roles along gender lines, thus perpetuating gender stereotypes. The results of this research study can be used in creating more appropriate curriculum for Home Economics Education in both primary and secondary level to inculcate the financial management practices and eventually help in eliminating gender stereotypes within households.
Thesis Classification: F
Thesis (B.S. Home Economics)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Finance, Personal -- Philippines